DOES NUCLEAR POWER HAVE A FUTURE? (Utah Environmental Law Review; Vol 32 No 2 (2012), 2012)
The simple answer to the question posited by the title of this Article is “Yes.” The safety, environmental, economic, and legal reasons underpinning this affirmative response are reasonably straightforward. This Article will define and delineate the most compelling of those reasons. When all costs and externalities are appropriately evaluated, the utilization of controlled nuclear fission as the basis for the commercial generation of electric power in the United States is cost-effective and safe. The public health and safety and environmental impacts of reasonably evaluated worst-case accident scenarios hypothesized for the new generation of domestic reactor designs are manageable, with the most significant consequences being economic. The regulatory requirements for new power reactors effectively preclude the release of significant quantities of radioactive materials from foreseeable events and postulated accidents. Whereas current experience indicates that nuclear power is very safe relative to other methods of generating electricity, the consideration of safety and improvements of new designs combined with the assessment of relative risk associated with major energy sources, as discussed hereinafter, indicates that facilities under construction or undergoing regulatory approval are at least two, and in most cases four, orders of magnitude lower in risk to the health and safety of the public than currently operating electricity-generating facilities fueled by fossil fuels.